Differential Use of Game Species in an Amazonian Indigenous Community: Navigating Economics, Subsistence, and Social Norms. Issue Volume 42:Issues 3(2022) (September 2022) - Griffiths, Brian M.; Gilmore, Michael P.
Hunting is a key subsistence strategy and source of income and food security for rural communities throughout the world. Hunters often gift game meat to their friends or family in return for reciprocation or other social benefits. We used interviews to assess how hunters in an Amazonian Indigenous community navigate the economic, subsistence, and social aspects of hunting. We found that hunters typically sell the most valuable and preferred species whole, except for the head, gift better cuts of less-preferred species, and consume the lowest quality portions of non-preferred species. We conclude that hunters use species and portions of carcasses differentially to maximize profit and food security and fit the social norms of the community. Understanding the social systems surrounding wild game use in rural Amazonian communities provides insight into how the loss of wild mammals could influence food security and social relationships.